MODERASI NPM TERHADAP PENGARUH CR, DER, DAN TATO ATAS HARGA SAHAM EMITEN INDUSTRI PARIWISATA DAN REKREASI - Fitri, Fitri; Lumbanraja, Maha Martabar Mangatas; Ferdiansyah, Ferdy (Jurnal Daya Saing, 2025)
This research is motivated by the increasing number of foreign and domestic tourist visits to Indonesia which has an impact on improving the company's financial performance and should also have an impact on increasing stock movements, but initial findings indicate a correction in the tourism sector composite index. The sampling technique used purposive sampling with a sample size of 33 out of a total of 49 emitens. This research is a quantitative study, with secondary data sources, which were analyzed using the PLS approach. The results of the study indicate that the three causal variables are factors that influence changes in stock prices, where DER and TATO have a positive correlation. This study found that the total assets owned still rely too much on capital from investors in driving their businesses and have an impact on the low economic capacity of issuers. While CR has a negative correlation with changes in stock prices which confirms the existence of a negative signal for investors in companies that are too smooth which was found in this study. This study also found that the NPM variable is not a variable that is able to moderate the influence of the three independent variables on changes in stock prices